Research on medical education at San Fernando Faculty of Medicine: a systematic perpective - Mendoza-Arana, Pedro Jesús (2012)
Background: It is necessary to establish bases for research in medical education at San Fernando Faculty of Medicine. Identification of investigators working in medical education latu sensu in health educational research is expected, as well as research lines and methods used. Objectives: To identify investigators dedicated to education research in health, and to identify lines of research and main methodologic strategies. Design: Bibliography review of articles y abstracts on health education. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Investigators in health education. Methods: Participating units were the Faculty of Medicine’s thirteen academic departments and six institutes. Main outcome measures: Lines of medical research, investigators, methods, types of publication. Results: Main research lines in medical education were: Teaching-learning methods, Education on research, Ethics, Students’ characteristics, Admission/Graduation, and Curricular research. Research on education administration is not currently developed. Only 25% of production became articles, 75% were summaries. Main research units in medical education were Dynamic Sciences, Preventive Medicine, and Nursing School academic departments; and among Institutes, the Institute of Ethics. Research is done by teams in 80% of cases, mostly constituted by 3 to 6 teachers. There was an important student contribution through Sociedad Cientifica de San Fernando. Methods used were usually descriptive designs and case studies. Conclusions: We appeal to articulate Faculty’s research on medical education experience and ability with the agenda of priorities of investigation on human resources in health established by the Ministry of Health.